In vitro toxicity, antioxidant, anti-inflammatory, and antidiabetic potential of Sphaerostephanos unitus (L.) holttum - Johnson, MAA (2020)
Pteridophytes have been widely used in several systems of medicine. Several reports have increasingly assessed their bioactive effects, but for Sphaerostephanos unitus (L.) Holttum, only its antibacterial potential has been assessed. In this sense, the present study was carried out to reveal the phytochemical profile and to determine the toxicity, antioxidant, antidiabetic, and anti-inflammatory potential of S. unitus. Brine shrimp lethality, 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, phosphomolybdenum assay, superoxide radical scavenging activity, 2,2-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) assay (ABTS), and in vitro a-amylase inhibitory and membrane stabilization assays were applied. S. unitus extract toxicity showed variable mortality percentages, with LC50 values ranging from 4 to 30 mg/mL. DPPH radical scavenging effects of S. unitus extracts were as follows: methanol > acetone > petroleum ether > chloroform. S. unitus acetone extract displayed the strongest phosphomolybdenum reduction (10 ± 2 mg Ascorbic Acid Equivalent/g). The studied extracts also revealed efficient, superoxide scavenging effects in a dose-dependent manner. In S. unitus, the highest ABTS radical scavenging rate was observed in the chloroform extract (3000 ± 40 µmol/g). The S. unitus anti-inflammatory effect was as follows: petroleum ether > chloroform > methanol > acetone. In S. unitus extract, the highest percentage of a-amylase activity (80%) was observed for the petroleum ether extract (25 µg/mL). Faced with these findings, further studies should be performed to isolate and identify the S. unitus compounds responsible for their antioxidant, antidiabetic and anti-inflammatory effects.